PERBANDINGAN STRUKTUR ADEGAN PAKELIRAN WAYANG KULIT PURWA GAYA SURAKARTA DAN YOGYAKARTA - Sudarko Sudarko (Institut Seni Indonesia Surakarta, 2010)
This paper will seek for similarities and diversities of scene structures in shadow puppet pakeliran, Surakarta and Yogyakarta styles. Besides, it also explains the causes that make similarities and diversities in shadow puppet pakeliran of the two styles. The writer uses comparative approach in finding similarities and diversities of scene structures in shadow puppet pakeliran of the two styles and historical approach in seeking causes that make similarities and diversities in scene structures. The similarities of scene structures in shadow puppet pakeliran, Surakarta and Yogyakarta styles include (1) the two styles consist of three pathet: pathet nem, sanga, and manyura, (2) each pathet consists of three kinds of scenes, they are (a) jejer, (b) two or more scenes caused by jejer, and (c) war. The cause of similarities is that the two styles come from the same culture, Mataram. The difference of scene structure in shadow puppet pakeliran of Surakarta and Yogyakarta styles is: (1) shadow puppet pakeliran of Surakarta style has limbukan but Yogyakarta style doesn’t have it, (2) the scene og gara-gara has to be executed in Yogyakarta style but it doesn’t have to be in Surakarta style. The differences emerge because of the break of Mataram Palace becomes two palaces, Surakarta Hadiningrat and Yogyakarta Hadiningrat. For the next, each palace eagerly shows its own identity by developing their local cultures. Key words : pedalangan, shadow puppet, style